Goal Orientation and Learning Readiness: Evidence Among Freshmen in Selected Kenyan Universities - Mose, Evelyne Kwamboka; Aloka, Peter JO; Mwebi, Benard (AJER, 2022)
This study, which adopted an ex post facto research design, investigated the relationship between goal orientation and learning readiness among first year students in three public universities in Kenya. A sample size of 372 first years from the three universities were obtained using both stratified and simple random sampling techniques. The Goal Questionnaire for Students (GQS) and the Learning Readiness Questionnaire (LRQ) were used to collect data. The findings reported Eta squared (.547) which implied that a fairly large proportion (54.7%) of variance in the learning readiness index among the first year students is explained by goal orientation of the students. Results from the study determined that universities should emphasize techniques of performance approach in their guidance programs.
Keywords: Goal Orientation; Learning Readiness; First Year; Students; Universities; Kenya